The Holy People of God. Identity, Contexts, Challenges Svetlana Khobnya, Arseny Ermakov, Deirdre Brower Latz, Peter Rae and MiJa Wi (eds): Eugene: Pickwick, 2024; xx + 243 pp, pb, £29.00; ISBN 978-1-6667-7271-5 - Wilson, Paul E. (2025)
This Festschrift for Dr Kent Brower contains a vibrant and diverse range of essays that explore the concept of social holiness in biblical studies, theology and missiology. While most valuable for those in Wesleyan traditions or people influenced by Brower’s work, the book offers crucial insights for anyone interested in holiness as more than individual piety and provides excellent resources for navigating challenges in society, Church and theological education.
Keywords: Rezension